PENGARUH BLOTONG, ABU KETEL, KOMPOS TERHADAP KETERSEDIAAN FOSFOR TANAH DAN PERTUMBUHAN TEBU DI LAHAN TEBU PABRIK GULA KEBON AGUNG, MALANG - Dery Pambudi; Maulana Indrawan; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2017)
The main problem in the Karangduren sugarcane soil is the low availability of soil-P that leads to the low of cane production. The objectives of this study was to determine the effects of filter-cake, sugarcane boiler ash and compost on availability of soil-P and growth of sugarcane at Kebon Agung Sugar Mill in Karangduren village of Malang. The treatments tested were control (P0), sugarcane boiler-ash 60 t ha-1 (P1), compost 3 t ha-1 (P2), filter-cake 60 t ha-1 (P3), sugarcane boiler ash 30 t ha-1 + filter cake 30 t ha-1 (P4), sugarcane boiler ash 15 t ha-1 + filter-cake 45 t ha-1 (P5), and sugarcane boiler ash 30 t ha-1 + filter-cake 30 t ha-1 + bio-fertilizers 80 L ha-1 (P6). Results of the study showed that application of sugarcane boiler ash, filter cake and compost improved chemical characteristics of the soil studied and increased growth of sugarcane up to 4 MAP (months after planting). The best treatment in improving soil chemical characteristics and growth of sugarcane was application of sugarcane boiler ash 60 t ha-1 (P1). Application of sugarcane boiler ash 60 t ha-1 was able to increase soil pH by 6.12%, increasing the content of soil C-Organic by 46.03 % and soil-P availability by 328.39 % compared to soil before treatment. Application of sugarcane boiler ash 60 t ha-1 (P1) was also able to improve growth of sugarcane measured by the cane height, cane length, number of shoots, number of leaves, content of chlorophyll, cane dry weight and P-uptake of sugarcane.Â